Evaluation of Calculation Algorithms for photon Beam dose in Heterogeneous Medium (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The success of the implementations of a radiotherapy treatment planning system is determined by the ability of the dose calculation algorithms to reproduce the algorithm input data, and in most cases the agreement was found within Â±2%. Varian linear accelerator DMX, TPS Eclipse (version 10.33) is used and absolute dosimetry and relative dosimetry system (PTW, Freiburg, Germany) and 2D array were also used. The Calculation of Analytical Anisotropic Algorithm (AAA) is more accurate than the Pencil beam Algorithm (PBC) in heterogeneity medium in comparison with practical measurement. The extent of the effort required to carry out a validation study of the complexity of that described here precludes its use as a routine component of TPS commissioning. Our realistic recommendation is that commissioning includes tests aimed at confirming that raw beam data have been entered correctly and that the operation of the system is understood. Finally, the study tell us that the observed deviations between TPS calculated using Eclipse version 10.33 and measured dose in the present of heterogeneous medium are well within the tolerance levels and the study also show that the use of Eclipse (version 10.33) TPS, AAA algorithm records significant improvement than the previous TPS versions especially in the present of low density inhomogeneity.